Trends and determinants of caesarean section in South Asian countries: Bangladesh, Nepal, and Pakistan. - Md Sohel Rana; Shrabanti Mazumder; Md Tareq Ferdous Khan; Md Mobarak Hossain Khan; Md Mijanur Rahman (PLoS ONE)
Background The prevalence of caesarean sections (C-sections) has remarkably increased in the past few decades worldwide, especially in the lower and middle-income countries (LMICs). To our best knowledge, no studies focused on and compared the C-section scenarios of Bangladesh, Nepal, and Pakistan based on the latest demographic and health survey (DHS) data. Objectives To assess the trends and factors associated with C-sections in the three South Asian countries. Study population Mothers aged 15-49 years participated in DHS 1990 to 2017-2018 and gave birth within three years of each of the surveys in Bangladesh, Nepal, and Pakistan. Materials and methods This study analyzed data from five recent DHS rounds in Bangladesh and four in Nepal and Pakistan. Multivariable logistic regression was used to assess the association between C-sections and sociodemographic characteristics. Results The results show that institutional delivery and C-sections have increased throughout the period in all three countries. In Bangladesh, the hospital birth rate increased from 10.0% in 2004 to 49.9% in 2017, and the corresponding figures [S1 Appendix: Figure A1 and Figure A2] for C-sections increased from 3.5% to 32.8%. In Nepal, the hospital birth rate increased from 11.0% in 2001 to 58.6% in 2016, and the C-sections from 0.8% to 11.0%. Pakistan observed a sharp increase from 13.7% to 66.3% and 2.7% to 22.3% in the respective cases from 1990 to 2017. Results from regression reveal that the mother's age, place of residence, education, partner's education, wealth status, birth order, number of antenatal care visits, and body mass index are associated with C-section deliveries in all three countries. Conclusions Our findings regarding the association of sociodemographic factors with increased C-sections may help identify subgroups of women susceptible to C-sections and offer better support regarding C-sections plans. However, the substantial increase in C-sections across the three countries warrants further investigation to identify the reasons.